Bioaktivitas dan Aktivitas Antioksidan Ekstrak Batang Mahkota Dewa (The Bioactivity and Antioxidant Activity of Stem Extracts of Mahkota Dewa) - Ganis Lukmandaru; Anisa A Gazidy (Jurnal Ilmu dan Teknologi Kayu Tropis, 2016)
Mahkota Dewa [Phaleria macrocarpa (Scheff) Boerl.] is commonly used by Indonesian for medicinal purposes. This study elucidated the bioactivity and antioxidant activity of mahkota dewa stem and extractive compound analysis. The base part stem powder of 40 mesh was extracted successively with n-hexane, ethyl acetate, methanol, and hot-water. The analysis of extractive compound consisted of identification of secondary metabolites by chemical reaction, colorimetric, and gas chromatography – mass spectrometry (GC-MS). Bioactivity experiments involved antitermitic test to dry-wood termites (Cryptotermes cynocephalus Light) and brine shrimp lethality test (BSLT). Antioxidant activity was examined by 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The analysis of extractive compound by qualitative method showed that terpenoid, steroid, alkaloid, and saponin were detected. Further, the quantitative analysis showed the low level of total phenolic compound while flavonoids were not detected. GC-MS analysis showed that the 11 main components was dominated by fatty acid methyl esters. The n-hexane and ethyl acetate soluble fractions were toxic to dry-wood termites (termites mortality of 41-95%) and exhibited the lowest weight loss of paper disc (0.37-1.60 mg). BSLT showed that all fractions were highly toxic (LC50 ≤30 ppm). DPPH method gave the level of antioxidant activity in relatively low inhibition values (7.59-18.12%).